A multi-scale model explains oscillatory slowing and neuronal hyperactivity in Alzheimer's disease. Issue 198 (4th January 2023) - Alexandersen, Christoffer G.; de Haan, Willem; Bick, Christian; Goriely, Alain
Abstract : Alzheimer's disease is the most common cause of dementia and is linked to the spreading of pathological amyloid- β and tau proteins throughout the brain. Recent studies have highlighted stark differences in how amyloid- β and tau affect neurons at the cellular scale. On a larger scale, Alzheimer's patients are observed to undergo a period of early-stage neuronal hyperactivation followed by neurodegeneration and frequency slowing of neuronal oscillations. Herein, we model the spreading of both amyloid- β and tau across a human connectome and investigate how the neuronal dynamics are affected by disease progression. By including the effects of both amyloid- β and tau pathology, we find that our model explains AD-related frequency slowing, early-stage hyperactivation and late-stage hypoactivation. By testing different hypotheses, we show that hyperactivation and frequency slowing are not due to the topological interactions between different regions but are mostly the result of local neurotoxicity induced by amyloid- β and tau protein.